Yes, Ronald Reagan's Rhetoric Was Unique-But Statistically, How Unique? - SCHONHARDT‐BAILEY, CHERYL; YAGER, EDWARD; LAHLOU, SAADI (Presidential Studies Quarterly, 2012)
We use automated textual analysis to compare Ronald Reagan's rhetoric with that of presidents Woodrow Wilson through Barack Obama, using their State of the Union speeches. We are able to assign statistical significance to the thematic content, and to depict spatially the shifting dimensionality in themes used by presidents. We find strong evidence for Reagan's usage of the civil religion rhetoric: over half (59%) of the discourse in his seminal and 48% in his State of the Union speeches focus on civil religion. We also find an apparent shift in modern presidential rhetoric, from themes concerned with (1) institutions, to ones focused more on (2) individuals, families, and children.